The Effect Of Compensation On Employee Performance At Pt. Erajaya Swasembada TBK - Desfitrina Desfitrina; ZulFadhli ZulFadhli; M. Chandra WK (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
This study aims to determine the effect of compensation (X) on employee performance (Y) at PT.Erajaya Swasembada Tbk. data collection was carried out by distributing questionnaires to 35 respondents of PT.Erajaya Swasembada Tbk employees in the sales / promoter section. Data analysis used in this research is Quantitative analysis and Qualitative analysis, with simple linear regression test. Based on the results of the study, it shows that there is an influence of compensation on employee performance at PT.Erajaya Swasembada Tbk,. This is indicated by the results of the regression coefficients having a positive value, namely (0.411) with the Simple Linear Regression equation Y = 14.502 + 0.411X where if the independent variable (Compensation) increases by 1% then the dependent variable (Performance) also increases by 0.411%. and also vice versa. This states if the compensation variable partially has an influence on employee performance at PT.Erajaya Swasembada Tbk, And the results of this study indicate that compensation has an influence on employee performance by 29% while the remaining 71% is influenced by other factors not explained in this study.